MRI criteria differentiating asymptomatic PML from new MS lesions during natalizumab pharmacovigilance. Issue 10 (16th August 2016) - Wijburg, Martijn T; Witte, Birgit I; Vennegoor, Anke; Roosendaal, Stefan D; Sanchez, Esther; Liu, Yaou; Martins Jarnalo, Carine O; Uitdehaag, Bernard MJ; Barkhof, Frederik; Killestein, Joep; Wattjes, Mike P
Abstract : Objective: Differentiation between progressive multifocal leukoencephalopathy (PML) and new multiple sclerosis (MS) lesions on brain MRI during natalizumab pharmacovigilance in the absence of clinical signs and symptoms is challenging but is of substantial clinical relevance. We aim to define MRI characteristics that can aid in this differentiation. Methods: Reference and follow-up brain MRIs of natalizumab-treated patients with MS with asymptomatic PML (n=21), or asymptomatic new MS lesions (n=20) were evaluated with respect to characteristics of newly detected lesions by four blinded raters. We tested the association with PML for each characteristic and constructed a multivariable prediction model which we analysed using a receiver operating characteristic (ROC) curve. Results: Presence of punctate T2 lesions, cortical grey matter involvement, juxtacortical white matter involvement, ill-defined and mixed lesion borders towards both grey and white matter, lesion size of >3 cm, and contrast enhancement were all associated with PML. Focal lesion appearance and periventricular localisation were associated with new MS lesions. In the multivariable model, punctate T2 lesions and cortical grey matter involvement predict for PML, while focal lesion appearance and periventricular localisation predict for new MS lesions (area under the curve: 0.988, 95% CI 0.977 to 1.0, sensitivity: 100%, specificity: 80.6%). Interpretation: The MRI characteristics of asymptomatic natalizumab-associated PML lesions proved to differ from new MS lesions. This led to a prediction model with a high discriminating power. Careful assessment of the presence of punctate T2 lesions, cortical grey matter involvement, focal lesion appearance and periventricular localisation allows for an early diagnosis of PML.